Incidencia del pensamiento espacial y visual en la enseñanza aprendizaje de la geometría en grado tercero - Rodríguez Cabezas, Diana Katherine (Universidad Antonio Nariño, 2022)
Geometry is one of the most important branches in mathematics (Dindyal, 2015), that is why the traceability over the school years is pretty important, generating skills in students, without forgetting the teacher's training, interest and motivation, to understand the content. This thesis contributes to the teaching-learning process of geometric content, through spatial and visual thinking in third grade students of the Colegio Parroquial Santa Isabel de Hungría.